A fractal contact theory based model for bolted connection looseness monitoring using piezoceramic transducers - Huo, Linsheng; Wang, Furui; Li, Hongnan; Song, Gangbing (Smart materials and structures, 2017)
In this paper, based on the fractal contact theory, a new analytical model for bolted joints is proposed to monitor bolt looseness by using a pair of piezoceramic transducers for ultrasonic wave generation and detection. The time reversal method is used to obtain the focused signal peak amplitude during ultrasonic wave propagation through bolt connection surface. The influence of bolt load on the actual contact area of the bolted joint surface is determined by the fractal contact theory, and the finite element method is applied to obtain the relationship between the actual contact area and the focused signal peak amplitude. The focused signal peak obtained through the time reversal method increases with the increase of applied axial load before saturation. The investigation proposed in this paper is based on the inherent contact mechanism between the two contact surfaces, and achieves more accurate quantitative monitoring of bolt looseness. Finally, a comparison of the predicted and experimental results shown validates the proposed model in this paper.